Supporting Orientation During Search Result Examination - Feild, Henry; White, Ryen W.; Fu, Xin (ACM SIGCHI Conference on Human Factors in Computing Systems (CHI 2013), April 27-May 2, 2013, Paris, France, 2013)
Search engines help their users decide which results to visit using captions comprising titles, URLs, and snippets containing the query keywords and proximal text from landing pages (the search results linked from the result page). Although caption content can be a key factor in these decisions, snippets provide only basic support for orienting users with landing page content from the search-engine result page (SERP), and no support during the transition to landing pages or once users reach the page following a selection decision. As a result, many searchers must employ inefficient strategies such as skimming and scanning the content of the landing page. In this paper we propose a novel method, called clickable snippets, to address this shortcoming. Clickable snippets provide searchers with a direct and actionable link between SERP captions and landing-page content. We describe a user study comparing clickable snippets with extant methods of orientation support such as query-term highlighting on the landing page and thumbnail previews on the SERP. We show that clickable snippets are preferred by participants, and lead to more effective and efficient searching. Our findings have implications for the design of the user experience in search systems.